1995
DOI: 10.1002/nt.2620030504
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of a compound from avocado (Persea americana) leaves which causes necrosis of the acinar epithelium of the lactating mammary gland and the myocardium

Abstract: It is well known that when lactating livestock eat avocado (Persea americana) leaves they may develop non-infectious mastitis and agalactia. This is associated with extensive coagulation necrosis of the secretory acinar epithelium and interstitial oedema, congestion, and haemorrhage. Similar lesions have been produced in mammary glands of lactating mice fed a diet containing a small percentage of freeze-dried avocado leaf. Tests using these animals have been used to isolate the active principle, termed "persin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 18 publications
2
60
0
Order By: Relevance
“…This extract is associated with congestive heart failure related to severe cardiomyopathy in goats, horses and sheep. The plant leaves are reported to have caused severe cardivascular and lung damage and death in goats Oelrichs et al, 1995;.…”
Section: Persea Americanamentioning
confidence: 99%
“…This extract is associated with congestive heart failure related to severe cardiomyopathy in goats, horses and sheep. The plant leaves are reported to have caused severe cardivascular and lung damage and death in goats Oelrichs et al, 1995;.…”
Section: Persea Americanamentioning
confidence: 99%
“…The epithelium did not appear to regenerate, and more severely damaged tissue was replaced by scar and adipose tissue (Oelrichs et al, 1995). These results, correlating with the effects of ingestion of avocado leaves, suggest that persin is likely the most notable toxin in avocado leaves (Oelrichs et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…This observation led to the isolation of persin, an unsaturated fatty acid, closely related in structure to the essential fatty acid linoleic acid and exhibiting necrotic activity in the R configuration (Oelrichs et al, 1995). One study found that treatment with 60-100 mg/kg of persin has the same effect on lactating mice as ingestion of avocado leaves: interstitial edema, congestion, hemorrhage, and coagulative necrosis and shedding of the mammary gland epithelium (Oelrichs et al, 1995). The epithelium did not appear to regenerate, and more severely damaged tissue was replaced by scar and adipose tissue (Oelrichs et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations